Maximal and submaximal isometric torque is elevated immediately following highly controlled active stretches of the hamstrings - Chapman, N.; Whitting, J.; Broadbent, S.; Crowley-McHattan, Z.; Meir, R. (Journal of Electromyography and Kinesiology, 2021)
Hamstring strain rehabilitation programs with an eccentric bias are effective but have a low adherence rate. Post-stretch isometric (PS-ISO) contractions which incorporate a highly controlled eccentric contraction followed by an isometric contraction resulting in elevated torque during following stretch, compared with isometric contractions at the same joint angle. This study measured torque, activation and musculotendinous unit behaviour of the hamstrings during PS-ISO contractions of maximal and submaximal levels using two stretch amplitudes. Ten male participants (24.6 years ± 2.22 years) completed maximal and submaximal baseline isometric contractions at 90°, 120° and 150° knee flexion and PS-ISO contractions of maximal and submaximal intensity initiated at 90° and 120° incorporating active stretch of 30° and 60° at 60°·s-1. Torque and muscle activation of the knee flexors were simultaneously recorded. Musculotendinous unit behaviour of the biceps femoris long head was recorded via ultrasound during all PS-ISO contractions. Compared with baseline, torque was 8% and 39% greater in the maximal and submaximal PS-ISO conditions respectively with no change in muscle activation. The biceps femoris long head muscle lengthened during all PS-ISO contractions. PS-ISO contractions may be beneficial where the effects of highly controlled eccentric contractions and elevated isometric torque are desired, such as hamstring rehabilitation.